Research Trends on Local Potential and Opportunities in Science Education: A Bibliometric Analysis Using VOSviewer - Lestari, Wiwit Yuli; Surtikanti, Hertien Koosbandiah; Rahman, Taufik; Riandi (PT Mattawang Mediatama Solution, 2024)
Local potential refers to everything a region possesses in various fields, such as natural environment, resource production, culture, society, and other areas. This study aims to conduct a bibliometric analysis by integrating mapping analysis using the VOSviewer program and data collection using the Publish or Perish application. The method used is a bibliometric and quantitative descriptive approach. Data was obtained by searching for the terms